Ten-year epidemiology of ankle injuries in men's and momen's collegiate soccer players - Gulbrandsen, M.; Hartigan, D. E.; Patel, K. A.; Makovicka, J. L.; Tummala, S. V.; Chhabra, A. (Journal of Athletic Training, 2019)
Context Data from the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) have indicated that ankle injuries are the most common injuries among NCAA soccer players.